Potentiation of the antimicrobial effect of Lactobacillus reuteri DSM 17938 cell-free extracts by ascorbic acid. - O. V. Knysh; A. V. Martynov (Medičnì Perspektivi)
The purpose of this study was to evaluate the effect of supplementing the culture medium with ascorbic acid on the antimicrobial properties of Lactobacillus reuteri cell-free extracts (CFEs). CFEs were prepared using commercial strain L. reuteri DSM 17938 by culturing lactobacilli in its own disintegrated cell suspension (DCS) supplemented with ascorbic acid in sub-inhibitory (5 mg/ml, CFE5) or minimal inhibitory concentration (20 mg/ml, CFE20) and without supplementation (CFE0). Staphylococcus aureus AТСС 25923, Escherichia coli AТСС 25922 reference strains and Pseudomonas aeruginosa extensively drug resistant (XDR) clinical isolate were used as indicator cultures. Screening of the inhibitory properties of the studied CFEs and elucidation of the nature of inhibitory products were done using modified Micro scale Optical Density Assay (MODA). The inhibition indices (InhI) were calculated for the studied CFEs and ascorbic acid of appropriate concentrations. CFEs were subjected to HPLC-analysis. CFE5 and CFE20 showed significantly higher antimicrobial activity toward to indicator cultures than CFE0. InhI calculated for extracts CFE5 and CFE20 mainly exceeded the sum of the corresponding indicators calculated for CFE0 and ascorbic acid (АА) of appropriate concentrations: InhICFE5 ≥ InhI CFE0 + InhI AA5; InhICFE20 > InhI CFE0 + InhI AA20. Acidic metabolic products have made the greatest contribution to the antimicrobial effect of the studied CFEs. HPLC-nalysis showed that the modified ascorbic acid was the substance found in CFE20 in the greatest quantity. The revealed effect of potentiation of antimicrobial activity of CFEs by ascorbic acid should be taken into account when developing new biotechnological products based on derivatives of L. reuteri DSM 17938.